PENGARUH FASILITAS DAN AKSESIBILITAS TERHADAP MINAT BERKUNJUNG WISATAWAN DI PUNCAK PATO - Rahayu Paslina; Nini Sumarni (CV. ADIBA AISHA AMIRA, 2025)
This research aims to find out and identify how much influence facilities and accessibility have on tourist interest in visiting Puncak Pato. This type of research uses quantitative methods. The sample in this study consisted of 100 respondents. This research was processed with the help of IBM SPSS Statistics 29 software. Based on the results of hypothesis testing, it shows that the variables of facilities and accessibility simultaneously have a positive effect on tourists' interest in visiting Puncak Pato, with a significant value of 0.001 < 0.05. Partially, the facility variable has no effect on interest in visiting with a significant value of 0.097 > 0.05. The accessibility variable influences tourists' interest in visiting with a significant value of 0.000 <0.05. The results of this research show that: (1) partially the facility variable does not have a significant effect on tourists' interest in visiting Pucak Pato. The accessibility variable has a significant effect on tourist interest in visiting Puncak Pato (2) simultaneously the facility and accessibility variables have a positive and significant effect on tourist interest in visiting Puncak Pato